Altered Accuracy of Saccadic Eye Movements in Children with Fetal Alcohol Spectrum Disorder. (11th April 2013) - Paolozza, Angelina; Titman, Rebecca; Brien, Donald; Munoz, Douglas P.; Reynolds, James N.
Abstract : Background: Prenatal exposure to alcohol is a major, preventable cause of neurobehavioral dysfunction in children worldwide. The measurement and quantification of saccadic eye movements is a powerful tool for assessing sensory, motor, and cognitive function. The quality of the motor process of an eye movement is known as saccade metrics. Saccade accuracy is 1 component of metrics, which to function optimally requires several cortical brain structures as well as an intact cerebellum and brain‐stem. The cerebellum has frequently been reported to be damaged by prenatal alcohol exposure. This study, therefore, tested the hypothesis that children with fetal alcohol spectrum disorder (FASD) will exhibit deficits in the accuracy of saccades. Methods: A group of children with FASD ( n  = 27) between the ages of 8 and 16 and typically developing control children ( n  = 27) matched for age and sex, completed 3 saccadic eye movement tasks of increasing difficulty. Eye movement performance during the tasks was captured using an infrared eye tracker. Saccade metrics (e.g., velocity, amplitude, accuracy) were quantified and compared between the 2 groups for the 3 different tasks. Results: Children with FASD were more variable in saccade endpoint accuracy, which was reflected by statistically significant increases in the error of the initial saccade endpoint and the frequency of additional, corrective saccades required to achieve final fixation. This increased variability in accuracy was amplified when the cognitive demand of the tasks increased. Children with FASD also displayed a statistically significant increase in response inhibition errors. Conclusions: These data suggest that children with FASD may have deficits in eye movement control and sensory‐motor integration including cerebellar circuits, thereby impairing saccade accuracy.